SPECIFIC FEATURES OF THE PREPARATION OF RAW MATERIALS, MATERIALS AND INTERMEDIATES IN THE PRODUCTION PROCESS OF A NEWLY FORMULATED ACYCLOVIR TABLET - Xaydarov Vosil Rasulovich; Raximova Xusnidaxon Abdukarimovna (Journal Park Publishing, 2025)
This study describes the specific features of the preparation of raw materials and excipients, their qualitative assessment, and their further processing into intermediates in the industrial production process of a newly formulated acyclovir tablet. The physical and chemical properties of acyclovir are examined, together with the technological characteristics of auxiliary components used in pharmaceutical combination with it, including their sensitivity to moisture, particle size, flowability and compressibility. In developing the new composition, optimal ratios of substances were determined that ensure pharmacological activity, stability and technological adaptability. The efficiency of preparatory stages such as sieving, drying and homogenization of raw materials was investigated, as well as the necessary parameters during granulation and blending. Quality indicators of the intermediate product—uniform distribution, moisture content, bulk density and granule strength—were evaluated as key factors in ensuring the quality of the final tablet.
Keywords: Acyclovir tablets, pharmaceutical technology, raw material preparation, excipients, granulation process, particle size distribution, flowability and compressibility, moisture sensitivity, purified water system, intermediate product quality, tablet formulation stability, industrial tablet manufacturing.